2007
DOI: 10.1080/07434610600720442
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes for individuals who use augmentative and alternative communication: Part II – communicative interaction

Abstract: This study evaluated the communicative interaction skills of seven young men (ages 19-23 years) who had used AAC systems for at least 15 years. Turn-taking patterns, use of communicative functions, and linguistic complexity were analyzed. Current performance was compared to the participants' skills when they were preschoolers and participated in another study of interaction skills (Light, 1985; Light, Collier, & Parnes, 1985a,b,c). Results indicated that the turn distribution between partners was more equitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 21 publications
0
27
1
2
Order By: Relevance
“…Hamm and Mirenda (2006) examined long-term outcomes for eight participants with developmental disabilities and found that those with greater communicative competence also reported higher quality of life outcomes. Lund and Light (2006;2007a, 2007b) also reported retrospectively on the long-term outcomes of AAC intervention -this time with a cohort of participants with severe physical and speech impairments who had received AAC intervention over a 15-year period. They documented outcomes across various levels of the ICF model, including body functions, activities, and participation (e.g., receptive language, reading comprehension, communicative interaction, educational and vocational achievement, self-determination, quality of life).…”
Section: Focus On Long-term Outcomesmentioning
confidence: 99%
“…Hamm and Mirenda (2006) examined long-term outcomes for eight participants with developmental disabilities and found that those with greater communicative competence also reported higher quality of life outcomes. Lund and Light (2006;2007a, 2007b) also reported retrospectively on the long-term outcomes of AAC intervention -this time with a cohort of participants with severe physical and speech impairments who had received AAC intervention over a 15-year period. They documented outcomes across various levels of the ICF model, including body functions, activities, and participation (e.g., receptive language, reading comprehension, communicative interaction, educational and vocational achievement, self-determination, quality of life).…”
Section: Focus On Long-term Outcomesmentioning
confidence: 99%
“…Children who require augmentative and alternative communication (AAC) (e.g., communication boards, speech-generating devices) are at high risk for expressive language difficulties (e.g., Lund & Light, 2007). One particularly challenging transition is the shift from the use of single-to multi-symbol utterances; children using AAC tend to rely on single symbol messages to communicate (see Binger & Light, 2008, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…In the studies mentioned above, the partners frequently used a higher occurrence of closed or rhetorical questions, directives and requests for information with people who use AAC (Lund & Light, 2007). These elicit restricted responses compared to typical conversations where the use of "wh" and open questions is more prevalent.…”
Section: Communication Partners Using Closed Questions More Frequentlmentioning
confidence: 99%
“…(Carter & Maxwell, 1998;Downing, 2005;Lund & Light, 2007;Myers, 2007). Lund and Light (2007) (Light & Binger, 1998;Light et al, 1985). Obligatory conversational turns require a response such as open and closed questions; non-obligatory turns are those to which a response is optional, such as comments and statements.…”
Section: Dominance In Turn-taking By the Communication Partnermentioning
confidence: 99%
See 1 more Smart Citation